Unoccupied electronic states of Ru(0001) (2016)
This report presents a combined theoretical and experimental description of the unoccupied electronic states of Ru(0001), along the ΓM high symmetry direction of the Brillouin zone. A direct comparison between angleresolved inverse photoemission spectroscopy and ab initio calculations of the 3-dimensional (3D) electronic structure of Ru(0001) have been used to determine the energy dispersion and the identification of different states and surface resonances. Both, measurements and calculations, complement previous reports regarding the electronic structure of Ru.